A quantitative measure for alterations in the actin cytoskeleton investigated with automated high-throughput microscopy - Weichsel, Julian; Herold, Nikolas; Lehmann, Maik J.; Kräusslich, Hans-Georg; Schwarz, Ulrich S. (Cytometry, 2010)
The actin cytoskeleton modulates a large variety of physiological and disease-related processes in the cell. For example, actin has been shown to be a crucial host factor for successful infection by HIV-1, but the underlying mechanistic details are still unknown. Automated approaches open up the perspective to clarify such an issue by processing many samples in a high-throughput manner. To analyze the alterations in the actin cytoskeleton within an automated setting, large-scale image acquisition and analysis were established for JC-53 cells stained for actin. As a quantitative measure in such an automated approach, we suggest a parameter called image coherency. We successfully benchmarked our analysis by calculating coherency for both a biophysical model of the actin cytoskeleton and for cells whose actin architecture had been disturbed pharmacologically by latrunculin B or cytochalasin D. We then tested the influence of HIV-1 infection on actin coherency, but observed no significant differences between uninfected and infected cells. © 2009 International Society for Advancement of Cytometry
Online veröffentlicht am 6. November 2009
Gesehen am 18.10.2023